Food safety chemistry : toxicant occurrence, analysis and mitigation - Yu, Liangli; Wang, Shuo, 1969-; Sun, Baoguo, 1961- (Boca Raton : CRC Press, 2015)
'This edited book is a comprehensive guide to the chemistry of food toxicants produced during processing, formulation, and storage of food. Each major food chemical contaminant will be discussed for toxic effects and the biological mechanisms behind their toxicity. Their absorption and distribution profiles and the factors influencing their levels in foods will be discussed. In addition, a listing of commonly used analytical techniques in food safety chemistry will make the book useful for food scientists and nutritionists'--
'1 Food Safety Chemistry An Overview Haiqiu Huang and Liangli (Lucy) Yu 1.1 Introduction Food safety is of paramount importance to both consumers and food industry. According to Food and Agriculture Organization (FAO), food safety is defined as'absence or acceptable and safe levels of contaminants, adulterants, naturally occurring toxins or any other substance that may make food injurious to health on an acute or chronic basis.'1 In 2008, a perspective article published in the New England Journal of Medicine indicated that'globalization and international agribusiness allow problems with food supply to spread around the planet all too quickly,'2 which indicates that food safety has become a critical concern in human health and life quality worldwide regardless of the geological location or the degree of economic development. Up until now, the major attention of food safety has been given to food microbiology- related issues, which result from microorganism contamination and outbreak, and characterized by suddenness and unexpectedness. However, food microbiologyrelated issues are only one part of the food safety problems'--
Includes bibliographical references and index.
Keywords: Food adulteration and inspection; Food contamination; Food -- Analysis; Food -- Microbiology